Psycho-demographic factors influencing social and political activism in Nigeria - Azeez, Razaq Olugbenga; Olayemi, Oluwakemi; Iyunade, Olufunmilayo; Ifegbesan, Ayodeji Peter; Lawal, Moshood B. (Journal of Central and Eastern European African Studies, 2024)
Prior studies on social and political activism have neglected people’s demographic and pyschosocial factors, particularly in Nigeria. Thus, a n inquiry is garmane. This study used the world value data wave 7 collected between 2015-2020 for Nigeria, to assess the factors that determined participation in socio-political activism. The data were subjected to t-test, correlation, and regression analysis. A positive statistically significant correlation existed among gender, age, social class, and employment status, and interest in politics and participation in political activism, while negative correlation was found among educational level, geo-political region, and participation in political activism. A significant difference was found in participation and political activism based on social class, educational level, age, income, place, and marital status. No difference was found based on gender. Multiple regression analysis showed that the greatest potent set of predictors of participation in political activism are interest, gender, the highest level of education and marital status. The findings have germane implications for the realization of the Sustainable Development Goal 5.